2020
DOI: 10.3390/idr12030014
|View full text |Cite
|
Sign up to set email alerts
|

Panton-Valentine Leukocidin-Producing Staphylococcus aureus Infection: A Case Series

Abstract: Panton-Valentine leukocidin-producing Staphylococcus aureus (PVL-SA) is associated with relapsing multifocal skin and soft tissue infections (SSTI), necrotizing pneumonia (NP) and severe musculoskeletal infections. Epidemiology is underknown and underdiagnosis is likely. Recent travel abroad, case clustering and relapsing disease are often reported. We reviewed all cases of PVL-SA infection diagnosed at our center, and found 21 cases over a 43-month period. Most patients were adult males, had relevant travel h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Previous works have indicated that the male sex and comorbidities such as smoking, obesity and diabetes are risk factors for osteoarticular infections caused by SA PVL-producing strains [ 29 ]. In the present study, the lack of a statistically significant difference in the comparison of risk factors between the two groups could be due to the fact that the main risk factors for PVL match those for SA–PJI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous works have indicated that the male sex and comorbidities such as smoking, obesity and diabetes are risk factors for osteoarticular infections caused by SA PVL-producing strains [ 29 ]. In the present study, the lack of a statistically significant difference in the comparison of risk factors between the two groups could be due to the fact that the main risk factors for PVL match those for SA–PJI.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining two cases of PJI caused by the SA PVL-producing strains were chronic PJIs treated with a revision arthroplasty (one and two stage, respectively) and targeted antibiotic therapy for 12 weeks; these resulted in a 100% eradication rate in a medium follow-up of 24 months (range [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The surgical treatment, antibiotic regimens, and outcome of the total PJI cases are shown in Table S3.…”
Section: Clinical Outcomes and Microbiological Associationsmentioning
confidence: 99%
“…Esta modulación de la expresión de virulencia por la CC ocurre en cepas de S. aureus susceptibles a la CC, pero se abole en cepas con resistencia constitutiva CC. 12 Otra opción de tratamiento en infección por esta bacteria es el uso de inmunoglobulina humana que actúa sobre los efectos tóxicos de PVL. Un estudio in vitro de Gauduchon y colaboradores mostró que la inmunoglobulina humana neutraliza la formación de poros y el efecto citotóxico de la PVL.…”
Section: Continuación Del Caso Clínicounclassified
“…The predominance of CA MRSA in our study can be explained by the fact that people aged 0 to 30 years were most represented (59.7%). Younger people mostly carry CA MRSA, due to infrequent hospitalization [63]. In addition, factors like poor hygiene, socio-cultural habits in these regions of study may contribute to increased prevalence of S. aureus as it is easily transmitted by hand contact.…”
Section: Plos Onementioning
confidence: 99%